STUDENTS’ PERCEPTION TOWARDS THE USE OF CODE-SWITCHING USE IN EFL CLASSROOM - Bagus Maulana Hakim; Filly Arflida; Intan Satriani (PROJECT (Professional Journal of English Education), 2019)
As a foreign language in Indonesia, English is still difficult subject for majority of the Indonesian students, even though it has been taught in junior high school, senior high school, English course, and another education institution. Therefore, many English learning-teaching activities in Indonesia use code-switching. Code-switching is language change (switch) in communication, from one language to another, code-switching here means Indonesian to English or English to Indonesian. This research examined the students’ perception towards code-switching use in English Foreign Language (EFL) classroom. This research applied survey research method, and the instruments were consisted of questionnaire and interview session. Thirty students were involved in filling questionnaire and nine students were involved in both questionnaire and interview. The result showed that (1) majority of students agree on code-switching use in learning teaching activity (2) they perceive code-switching helps them in improving their listening skills (3) they give more respect to teachers who use code-switching when they teach (4) they consider code-switching use increases their chance in passing examination and (5) they feel more comfort and more confident when they study English.